Study of the accuracy of direct and indirect methods for measuring density on site - Caiza Cachumba, Brenda Nicole (2025)
The accurate determination of compacted soil density is essential to ensure the quality and stability of infrastructure works, especially in civil engineering projects where quality control is crucial. In this context, this research project was developed to evaluate the accuracy of direct and indirect methods for measuring the density of different types of soil in situ, using laboratory test benches. The main objective was to compare the accuracy of direct methods (sand cone, density, and unit weight) and indirect methods (nuclear densimeter and electrical densimeter) to determine parameters such as degree of compaction, moisture content, wet density, and dry density of compacted soils. To this end, soil samples were extracted and characterized and classified according to the Unified Soil Classification System (USCS) through granulometry, consistency limits, and plasticity index tests, verifying that they met the required properties. The methodology included the creation of test banks using the standard Proctor test and the application of selected methods to measure density in sands, silts, and clays. The results were statistically analyzed using standard deviation, coefficient of variation, normality analysis, and analysis of variance (ANOVA), supplemented with comparative tables and graphs. It was determined that direct methods were more accurate under controlled conditions, while indirect methods were more effective in terms of speed and ease of application. The conclusions allowed the advantages and limitations of each methodology to be identified, contributing to the selection of the most appropriate techniques for different applications in the field of engineering. This study contributed to the choice of more reliable methodologies for quality control in the construction of embankments or the compaction of structural layers of roads, optimizing processes and ensuring greater structural safety.